Kedudukan Etnis Tionghoa dalam Multikulturalisme Indonesia: Antara Harapan dan Kenyataan - Yeni Wijayanti (Jurnal Artefak, 2022)
This paper examines the position of the ethnic Chinese in multi-ethnic Indonesia. The dichotomy of natives (original citizens) and non-natives (citizens of Chinese descent) emerged since the Dutch colonial period, which is finally still embedded in the motherland. The purpose of this literature research is to reveal the position of the Chinese ethnicity in Indonesia. The method used is the historical method which includes heuristics, criticism, interpretation, and historiography. Data collection techniques are carried out using literature or literature studies. The research findings show that there are still ethnic Chinese in Indonesia who experience discrimination even though the government is trying to unite all ethnic groups. Regimes changed after colonialism disappeared from Indonesia, but the gap between the ethnic Chinese and the indigenous population still exists despite assimilation and integration efforts. This can be seen when a crisis occurs, ethnic Chinese are often the target of anger from the native population.